Multiple drug allergy syndrome in pregnancy: Lessons for sexual health physicians. (October 2021) - Mohamed Buhary, Thajunnisha; McGregor, Alastair; McSorley, John; Friday, Dawn
Co-existence of multiple drug allergies and pregnancy often results in vexing dilemmas for physicians. A 21-year-old pregnant woman presented with asymptomatic cervicitis with dual infection with Chlamydia trachomatis and Neisseria gonorrhoeae during her third trimester. She reported a history of generalised rash with mucous membrane involvement following use of both macrolides and penicillins. Her gonococcal infection was successfully treated with a single dose of intramuscular gentamicin and chlamydial infection with oral clindamycin and rifampicin.